Securitization, Ratings, and Credit Supply - DALEY, BRENDAN; GREEN, BRETT; VANASCO, VICTORIA (Journal of Finance, 2020)
ABSTRACT We develop a framework to explore the effect of credit ratings on loan origination. We show that ratings endogenously shift the economy from a signaling equilibrium, in which banks inefficiently retain loans to signal quality, toward an originate‐to‐distribute equilibrium with zero retention and inefficiently low lending standards. Ratings increase overall efficiency, provided that the reduction in costly retention more than compensates for the origination of some negative net present value loans. We study how banks' ability to screen loans affects these predictions and use the model to analyze commonly proposed policies such as mandatory “skin in the game.”